Routledge Handbook of Chinese Culture and Society, 1st edition - Latham, Kevin (Routledge, 2020)
The Routledge Handbook of Chinese Culture and Society is an interdisciplinary resource that offers a comprehensive overview of contemporary Chinese social and cultural issues in the twenty-first century.